FAKTOR RISIKO TERJADINYA KOINFEKSI TB PARU PADA PASIEN HIV/AIDS DI PUSKESMAS KOTA JAMBI TAHUN 2021-2024 - Tasya Novriani (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2026)
HIV and TB are public health issues that influence each other. Of all districts orcities in Jambi Province, Jambi City contributes the highest number of tuberculosiscases, accounting for 24.38% of all cases in Jambi Province. The total number ofTB co-infection cases in HIV patients in Jambi City in 2021-2024 is 57 cases. Ifthis situation continues, there will be even more deaths caused by TB coinfectioncases in HIV patients, as HIV patients with TB coinfection have a 1.8 times higherrisk of death compared to TB-free patients who are not infected with HIV. Thisstudy aims to analyze the risk factors for pulmonary TB coinfection in HIV/AIDSpatients at the Jambi City Community Health Center from 2021 to 2024. Theresearch method used was quantitative with a case-control study design. Thepopulation in this study consisted of all HIV/AIDS patients with pulmonary TBcoinfection (cases) and all HIV/AIDS patients (controls) at the Jambi CityCommunity Health Center who had cases in 2021-2024, with a total sample of 114patients. The sampling technique used was Health Facility Base Sampling. Dataanalysis used the Chi-Square test and Logistic Regression. Statistical test resultsshowed that the variables associated with the incidence of TB-HIV coinfection weregender (p= 0.039), contact history (p= 0.001), and occupation (p= 0.012). Theconclusion of this study is that gender, contact history, and occupation areassociated with the risk factors for pulmonary TB coinfection in HIV/AIDS patientsat the Jambi City Community Health Center from 2021 to 2024. Community healthcenters need to optimize contact screening and monitoring of HIV patients withsignificant risk factors and further research is needed to explore other variables thatmay influence TB coinfection in HIV patients.